FOXP3 polymorphisms in interstitial lung disease among Chinese Han population: A genetic association study. (22nd May 2017) - Yao, Jianyu; Zhang, Tianze; Zhang, Lili; Han, Kaiyu; Zhang, Linyou
Abstract: Introduction: Both genetic and environmental factors are implicated in the pathogenesis of interstitial lung disease (ILD). Single‐nucleotide polymorphisms (SNPs) in FOXP3 genes were implicated in the causation of some autoimmune diseases; however, association of these genes and ILD has not been reported. Objectives: To investigate whether FOXP3 polymorphisms are associated with ILD in a representative Chinese population. Methods: One hundred and fifty‐seven ILD patients and 170 healthy controls were recruited; SNPs were genotyped by the Sequenom MassARRAY platform and SHEsis was used to estimate the haplotype frequencies of SNPs. Results: The CC and TC genotypes of FOXP3 rs2280883 were associated with a significantly higher risk of connective tissue disease‐associated ILD (CTP‐ILD) than the TT genotype ( P  = .006). Patients with idiopathic interstitial pneumonia (IIP) showed a significantly higher frequency of rs3761547 (GG genotype) and rs3761549 (CC genotype) polymorphisms of FOXP3 as compared to that in controls ( P  = .038 and P  = .026, respectively). The rs2294021 (TC genotype) was less frequently observed among IIP patients as compared to that in controls ( P  = 0.029). In addition, the FOXP3 CAATC haplotype was associated with a greater risk for CTD‐ILD ( P =.048) as compared to controls, and the FOXP3 TCCCC haplotype showed an increased IIP risk ( P  = .001); however, patients with the FOXP3 TACTT haplotype showed a significant protective effect against IIP ( P  = .036). Conclusion: FOXP3 polymorphisms may be important markers to determine susceptibility to IIP or CTP‐ILD in Chinese population.